(untitled) (INNOVATIVE ECONOMY, 2021)
Kychko I.I., Gonta O.I., Muzyka V.V. ECOLOGICAL AND ECONOMIC IMPERATIVES FOR THE DEVELOPMENT OF FORESTRY, HUNTING AND WATER MANAGEMENT IN UKRAINE Purpose. The aim of the article is substantiation of the need to use the ecological and economic approach in the process of functioning of forestry, water, hunting in Ukraine. Methodology of research. The theoretical and methodological basis of writing the article are the fundamental provisions of economic theory, set out in the scientific works of domestic and foreign scientists on the efficiency (ecological and economic) use of forest, water resources and hunting grounds of Ukraine. General and special methods were used to solve certain tasks in the research process, in particular: analysis, synthesis, induction, deduction (to characterize the environmental and economic problems of forestry, water, hunting); abstract and logical (for the formation of conclusions and proposals on the need to use the ecological and economic approach and ecological rent as a direction of improving the ecological condition of forestry, water and hunting). Findings. It is argued that the economic, environmental, compensatory role of water and forest resources is growing, due to the man-made load on the environment in the world and in Ukraine. The content and algorithm of calculation of ecological rent as environment-forming value of forestry, water, hunting economy are determined. Problems of functioning and directions of development of forest, water, hunting economy are substantiated. Originality. Ecological and economic approach to the functioning of forestry, water, hunting in Ukraine was improved. This approach in contrast to the existing, allowed substantiating the need and developing an algorithm for using environmental rents as an environment of value of forest, water, hunting (monetary expression of ecological effect). Practical value. The use of the proposed ecological and economic approach allows to make informed decisions in the process of functioning of forestry, water hunting in Ukraine and to reduce the negative ecological consequences of nature management. Key words: forestry, water management, hunting management, ecological rent, ecological and economic approach, efficiency, nature management.